ORGANIZATION CULTURE, COMPETENCY, COMPENSATION, JOB SATISFACTION AND LECTURER LOYALTY - Nyoman Surya Wijaya; I Made Darsana; I Wayan Pantiyasa; I Nyoman Gede Astina (Institut Pariwisata dan Bisnis Internasional, 2018)
The synergy between tourism education institutions with the government is important to equate the perception that tourism as an independent science is a pride and a challenge for tourism college, including the International Bali Institute of Tourism (STPBI), which organizes vocational education programs. The role of the lecturer becomes very important in this stage. The problems in this research are 1). Does the organizational culture, competence, and compensation affect the job satisfaction of lecturers at STPBI 2). Does the job satisfaction, organizational culture, competence, and compensation affect the loyalty of lecturers at STPBI. This research uses a quantitative approach with Partial Least Square (PLS) analysis tools. The result are, organizational culture, competence, and compensation have positive and significant impact on the job satisfaction of lecturers. Job satisfaction, organizational culture and compensation have positive and significant impact on lecturers' loyalty. However, competence has no significant effect on lecturer's loyalty.